Rancang Bangun dan Implementasi Sistem Antrian Customer Pada PT. Infomedia Solusi Humanika - Rika Rosnelly; Dian Maya Sari; Cindy Paramitha (Jurnal Pengabdian Masyarakat Berbasis Teknologi, 2021)
The service process carried out at the customer care center is currently still using a manual service system. Therefore, the researcher tries to implement a customer queuing system at the care center to simplify the service process. In this final result the researcher will use the ATMega 16 microcontroller minimum system module for the design and manufacture of a minimum system to simplify the customer queuing service process at the care center. Microcontroller programming is widely used for service system display functions on seven segment displays as well as print out queue no. The process begins with the visitor pressing the push button which then the system will issue a print out of the visitor queue no. If the customer care servant presses the push button in the system used by the customer service, it is used for seven segment displays. Then the data from the push button results will be sent by the microcontroller to print out the queue no on the printer, and then enter the data into the Personal Computer. After that the waiter at the customer care presses the button then the data is sent by the microcontroller to be output on the seven segment display.